1995
DOI: 10.1172/jci117831
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic osmolytes in myelinolysis. A topographic study in rats after rapid correction of hyponatremia.

Abstract: IntroductionOrganic osmolytes have been implicated in the pathogenesis of myelinolysis because some of them are accumulated slowly during correction of chronic hyponatremia. I investigated whether there was a topographic correlation between demyelinative lesions and the regional changes of organic osmolytes after rapid correction of chronic hyponatremia.In normal female Sprague-Dawley rats, concentrations of glutamate, glutamine, taurine, and betaine were highest in the cerebral cortex and decreased toward the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…One important clue is that the distribution of astrocyte loss after ODS induction in this study seems to correlate with both the distribution of the main organic osmolyte transporter in the rat brain and the gradient of osmolyte depletion during chronic hyponatremia. 8,44 Another key observation was that supplementation with the osmolyte myo-inositol prevented experimental ODS 45 and astrocyte death upon hyperosmotic challenge in vitro. 46 By studying the temporal relationship between astrocyte and myelin loss, we showed that astrocyte death precedes demyelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important clue is that the distribution of astrocyte loss after ODS induction in this study seems to correlate with both the distribution of the main organic osmolyte transporter in the rat brain and the gradient of osmolyte depletion during chronic hyponatremia. 8,44 Another key observation was that supplementation with the osmolyte myo-inositol prevented experimental ODS 45 and astrocyte death upon hyperosmotic challenge in vitro. 46 By studying the temporal relationship between astrocyte and myelin loss, we showed that astrocyte death precedes demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the overshooting of the optimal sodium concentration in the brain occurs in the context of depleted organic osmolytes. 7 Interestingly, regional differences in organic osmolyte reaccumulation have been associated with particular patterns of demyelination in ODS, 8 but the mechanisms connecting impaired osmolyte reaccumulation, myelin loss, and the cells involved in this process remain elusive.…”
mentioning
confidence: 99%
“…In experimental models, brain regions that are slowest to recover osmolytes are the most severely affected by myelinolysis. 70 Uremia protects against myelinolysis and brain osmolytes are recovered more rapidly during correction of hyponatremia in animals that are uremic than in nonuremic animals. 71 Finally, infusion of myoinositol (a major osmolyte lost in the adaptation to hyponatremia) protects against mortality and myelinolysis from rapid correction of hyponatremia.…”
Section: Brain Adaptation To Hyponatremiamentioning
confidence: 99%
“…There are low concentrations of betaine in brain [30], and BHMT is not expressed in this tissue [31]. When folatedependent remethylation is disturbed, the brain becomes dependent on preformed methyl groups delivered as SAM.…”
Section: Betaine Supplementation To Lactating Dams Increases Betaine mentioning
confidence: 99%